PEMBERIAN URIN MANUSIA PADA BIBIT TANAMAN KELAPA SAWIT (Elaeis guineensis jacq) TAHAP PRE NURSERY - yulia, Arnis En; Yanti, Nurlinda '; ', Sampurno ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The objectives of this study was to determine the provision of human urine and get the best result for the growth of oil palm seedlings stage of pre nursery. Study has been carried out in the land of Plant Laboratory, Agriculture Faculty,University of Riau from June to October 2015. This study arranged experimentally using Completely Randomized Design (CRD), consist of 5 treatments and each treatment was repeated 4 times then obtained 20 experimental units. The treatment given is P0: Without giving human urine, P1: provision of human urine with a volume of 50 ml/polybag, P2: giving human urine with a volume of 100 ml/polybag, P3: giving human urine with a volume of 150 ml/polybag and P4: Giving human urine with a volume of 200 ml/polybag.Parameters measured were seedling height, number of leaves, stem diameter, root volume, crown root ratio and seeds dry weight. Data were analyzed statistically using analysis of variance and further test followed by Duncan's New Multiple Range Test (DNMRT) at the level of 5%. From the study that has been carried out,showed that giving of human urine on the growth of plant seedlings of palm oil (Elaeis guineensis jacq) at the stage of pre nursery significant affected on seedling height and number of leaves.The best treatment in the giving of human urine on the growth of seedlings of palm oil trees obtained in a volume of 200 ml/polybag and not significant with the treatment of 100 and 150 ml/polybag. Keywords: Human urine, Palm oil, Pre Nursery